Analisis Kebutuhan Fasilitas Lalu Lintas di Kawasan Industri (Sekitar Jl. Karaeng Patingalloang Kota Makassar) - Andi Miftahul Ulum; Hairuddin Hairuddin; Muh. Arifin; Rahmad Rahmad; Adnan Adnan (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Makassar industrial area has increased economic activity and traffic. The aim of this research is to evaluate and maximize the types of traffic facilities needed to facilitate safe and efficient mobility in the Makassar Industrial Area. Field surveys, traffic volume analysis, and evaluation of existing infrastructure were carried out to achieve research objectives. The research results show that, as vehicle volumes increase, especially heavy vehicles, road infrastructure and supporting facilities must be adjusted. Widening roads, adding signs and markings, optimizing the traffic management system, and providing pedestrian facilities and public road lighting are the main recommendations. Additionally, it was decided that pedestrian facilities, a good drainage system, and access to emergency vehicles were of the utmost importance. It is hoped that the implementation of these recommendations will improve security, reduce congestion, and encourage sustainable economic growth in the Makassar Industrial Area.